Acute Thoracolumbar Spinal Cord Injury: Relationship of Cord Compression to Neurological Outcome. (21st February 2018) - Skeers, Peta; Battistuzzo, Camila R.; Clark, Jillian M.; Bernard, Stephen; Freeman, Brian J.C.; Batchelor, Peter E.
Abstract : Background: Spinal cord injury in the cervical spine is commonly accompanied by cord compression and urgent surgical decompression may improve neurological recovery. However, the extent of spinal cord compression and its relationship to neurological recovery following traumatic thoracolumbar spinal cord injury is unclear. The purpose of this study was to quantify maximum cord compression following thoracolumbar spinal cord injury and to assess the relationship among cord compression, cord swelling, and eventual clinical outcome. Methods: The medical records of patients who were 15 to 70 years of age, were admitted with a traumatic thoracolumbar spinal cord injury (T1 to L1), and underwent a spinal surgical procedure were examined. Patients with penetrating injuries and multitrauma were excluded. Maximal osseous canal compromise and maximal spinal cord compression were measured on preoperative mid-sagittal computed tomography (CT) scans and T2-weighted magnetic resonance imaging (MRI) by observers blinded to patient outcome. The American Spinal Injury Association (ASIA) Impairment Scale (AIS) grades from acute hospital admission (⩽24 hours of injury) and rehabilitation discharge were used to measure clinical outcome. Relationships among spinal cord compression, canal compromise, and initial and final AIS grades were assessed via univariate and multivariate analyses. Results: Fifty-three patients with thoracolumbar spinal cord injury were included in this study. The overall mean maximal spinal cord compression (and standard deviation) was 40% ± 21%. There was a significant relationship between median spinal cord compression and final AIS grade, with grade-A patients (complete injury) exhibiting greater compression than grade-C and D patients (incomplete injury) (p < 0.05). Multivariate logistic regression identified mean spinal cord compression as independently influencing the likelihood of complete spinal cord injury (p < 0.01). Conclusions: Traumatic thoracolumbar spinal cord injury is commonly accompanied by substantial cord compression. Greater cord compression is associated with an increased likelihood of severe neurological deficits (complete injury) following thoracolumbar spinal cord injury. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.